Efficacy and safety of elbasvir/grazoprevir and sofosbuvir/pegylated interferon/ribavirin: A phase III randomized controlled trial - Sperl, Jan; Horvath, Gabor; Halota, Waldemar; Ruiz-Tapiador, Juan Arenas; Streinu-Cercel, Anca; Jancoriene, Ligita; Werling, Klara; Kileng, Hege; Koklu, Seyfettin; Gerstoft, Jan; Urbanek, Petr; Flisiak, Robert; et al. (Journal of hepatology, 2016)
BACKGROUND & AIMS: Direct-acting antiviral agents have improved treatment outcomes for patients with hepatitis C virus (HCV) infection; however, head-to-head comparisons are limited. The C-EDGE Head-2-Head Study compared the safety and efficacy of elbasvir/grazoprevir (EBR/GZR) with sofosbuvir plus pegylated interferon/ribavirin (SOF/PR) in patients with HCV infection. METHODS: This was a randomized, open-label, phase III trial. Two hundred fifty-seven patients with HCV genotype (GT)1 or 4 infection and baseline viral load >10,000IU/ml were randomized to receive 12weeks of EBR/GZR 50mg/100mg once daily (n=129) or sofosbuvir (400mg once daily) plus PR (n=128). Primary efficacy objective was sustained virologic response 12weeks after the end of therapy (SVR12, HCV RNA <15IU/ml). The primary safety objective was the proportion of patients experiencing a tier 1 safety event. RESULTS: The majority of patients were non-cirrhotic (83.1%), treatment-naïve (74.9%) and had HCV GT1b infection (82.0%). SVR12 rates were 99.2% (128/129) and 90.5% (114/126) in the EBR/GZR and SOF/PR groups, respectively. The estimated adjusted difference in SVR12 was 8.8% (95% confidence interval [CI], 3.6-15.3%). Because the lower bound of the 1-sided 1-sample exact test was greater than -10% and greater than zero, both non-inferiority and superiority of EBR/GZR vs. SOF/PR were established. The frequency of tier 1 safety events was lower among patients receiving EBR/GZR than SOF/PR (0.8% vs. 27.8%, between group difference, 27.0% [95% CI, -35.5% to -19.6%; p<0.001]). CONCLUSIONS: EBR/GZR has a superior efficacy and safety profile in patients with HCV GT1 or 4 infection compared with SOF/PR. LAY SUMMARY: The combination of elbasvir/grazoprevir for 12weeks was highly effective in treating patients with chronic hepatitis C, genotypes 1 or 4 infection. This regimen was more effective than sofosbuvir/pegylated interferon/ribavirin for 12weeks, and was notably superior in patients regarded as difficult to treat, including those with previous treatment failure, cirrhosis, or a high baseline viral load. The combination of elbasvir/grazoprevir also demonstrated a superior safety and tolerability profile based on fewer serious adverse events, no serious drug-related adverse events, and no treatment discontinuations. CLINICAL TRIAL REGISTRATION: Clinical trials.gov Identifier: NCT02358044.
Keywords: Hepatitis; RNA virová; Imidazoles; imidazoly; Humans; Hepatitis C, Chronic; Sofosbuvir; interferony; sofosbuvir; ribavirin; Genotype; lidé; Interferons; Benzofurans; chronická hepatitida C; Randomized; antivirové látky; benzofurany; Therapy; Antiviral Agents; Quinoxalines; RNA, Viral; genotyp; kombinovaná farmakoterapie; chinoxaliny; Ribavirin; Hepacivirus; Drug Therapy, Combination